The Amplitude and Frequency Spectrum of Cerebral Blood Flow Fluctuations in Hemorrhagic Shock - I. A. Ryzhkov; A. K. Kirsanova; Yu. V. Zarzhetsky (Общая реаниматология, 2014)
Objective: to study the mechanisms of changes in local cerebral blood flows in blood loss and after its replacement.Material and methods. Experiments were carried out on 24 outbred male rats weighing 400—550 g, anesthetized with nembutal or chloralhydrate. The caudal artery was catheterized to measure blood pressure (BP), to sample and reinfuse blood. Blood flow in the pial vessels of the left parietal region was recorded by laser Doppler flowmetry. Onehour hypovolemic hypotension followed by autoblood reinfusion served as a model. Blood loss volume necessitated maintenance of BP at about 50 mm Hg by 60 minutes of hypotension. The investigators determined the following indicators of local cerebral circulation: microcirculatory index (MI) and relative perfusion units (pf. u); a wavelet method was used to estimate the maximum amplitudes of blood flow fluctuations (flux motions) in the ranges accepted to be correlated with active and passive mechanisms to reulate microcirculation. The data were statistically processed by applying the Statistica 7.0 program. The results were presented as Me (25%; 75%).Results. According to BP at 60 minutes of blood loss, the animals were divided into 2 groups: 1) more than 50 mm Hg (compensated animals) and 2) less than 50 mm Hg (decompensated ones). The groups did not differ in blood loss amount. At 60 minutes of hypotension, both groups showed diminished cerebral blood flow relative to the outcome with a tendency towards a more marked reduction in the decompensated animals. Throughout the hypotension period, the compensated animals displayed an increase in the amplitude of flux motion in the range of 0.06-0.12 Hz both relative to the outcome and versus the decompensated rats (p<0.05). In the latter, this indicator did not differ from its baseline values throughout the period. After blood reinfusion, all analyzed indicators in the compensated animals did not differ from thebaseline values (p<0.05). The group of decompensated animals was characterized by a poor recovery period, which was reflected by the lower values of BP and MI and tension of compensatory mechanisms for regulation of microcirculation.Conclusion. With hypovolemic hypotension, the increased amplitude of flux motions in the pial vessels involves the animals' capacity to compensate BP and it is an individual typological feature of microcirculation. The weak ability of the decompensated rats to develop highamplitude flux motions restricts the processes of cerebral circulatory recovery in the reinfusion period.